Buku Kesehatan Ibu Dan Anak (Kia) Dengan Perkembangan Balita Usia 3-6 Bulan Di Posyandu Desa Pagar Jati Muara Enim - Irma Maharani; Nia Clarasari Mahalia Putri; Nurul Komariah; Asri Noviyanti; Aprilia Ayu SY (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
The importance of child development which includes increasing gross motor skills, fine motor skills, speech, language, as well as socialization and independence, where developmental disorders can hinder the achievement of growth and development according to age. To prevent developmental delays, stimulation carried out by mothers and families at home through the use of the KIA Book is one of the important efforts. However, there has been no research discussing the use of the KIA Book in Pagar Jati Village. This study aims to determine the relationship between the use of the Maternal and Child Health Book (KIA) and the development of toddlers aged 3-36 months at the Pagar Jati Village Posyandu. This study used an analytical survey design with a Cross Sectional approach, conducted in April-May 2024 with a sample of 33 mothers of toddlers selected through a purposive sampling technique. Data analysis used the chi-square test. The results showed that the majority of mothers at the Pagar Jati Village Posyandu utilized the KIA Book well (60.6%). Most of 69.7% showed development according to age. There is a significant relationship between the use of the KIA Book and toddler development (p value = 0.003). In conclusion, there is a positive relationship between the utilization of KIA Books and the development of toddlers aged 3-36 months, and these results can be important information to increase insight into toddler development among mothers and families.